God’s “Handing Over” as a Divine Curse: A New Reading of the παραδιδόναι Clause in Romans 1:24, 26, 28 - Kim, Seon Yong (Zeitschrift für die neutestamentliche Wissenschaft, 2021)
Attempts to unravel the thrice-repeated παραδίδωμι clause in Rom 1:18-32 have been surprisingly few. Against several interpreters who see God’s παραδιδόναι to be basically permissive or abandoning, the present essay seeks to show that reading the passage in light of ancient binding curses, where the verb παραδίδωμι was extensively employed as a terminus technicus , generates a cogent grasp of the text with regard to the tenor and discursive logic of Rom 1:18-32. God’s “handing over” is a divine cursing punishment, and the verb expresses God’s direct involvement in punishment.